Desenvolvimento de um mecanismo para enlonamento e desenlonamento automatizado de reboques graneleiros destinado ao setor de transporte rodoviário brasileiro - Lopes, Fabio de Abreu (2019)
The Brazilian road transport sector has been growing over the years as has the technology employed by the transport set however, the same did not occur proportionally to the procedures to cover and uncover tarpaulin trucks which still depend on human effort to be performed. The objective of this work was the development of a mechanism to automating the procedure of covering and uncovering trucks with tarpaulins aiming to reduce the working time of this stage prevent any fall hazards when the user is on the truck body placing or removing the tarpaulin and provide user convenience. For the elaboration of this mechanism was used the methodology described by Norton (2013) mathematical modeling for motor sizing and 3D modeling of a prototype. A 1:2 scale prototype of a standard body truck was developed for the necessary tests and validations prior to assembly in a real model. The results obtained were satisfactory attending all the established objectives, something very important for the next step that is to make a real model.